Effacing the self: mysticism and the modern subject - Kesel, Marc de (SUNY Series in Theology and Continental Thought, 2023)
Intro -- Contents -- List of Illustrations -- Introduction -- Fénelonian Promenades -- Chapter 1 Love's Intimate Violence: Selfless Love in Fénelon and Malebranche (and Robespierre) -- Agape -- Loving Is Willing -- Willing Is Loving -- A Violent "Self" -- Terrific Love . . . -- … for the State and for the People -- Chapter 2 Selfless: Eckhart, Fénelon and the Modern Subject -- Eckhartian Selflessness … -- … as "Subject" -- Modernity: A Change of Subject -- Mysticism and Modernity -- "On the Renunciation of the Self" -- "The interior voice" -- "Pure Love" -- The Pain of the Modern Martyrium -- Chapter 3 Love Thy Neighbor Purely: Mysticism and Politics in Fénelon -- Pur Amour and Neighborly Love -- Fénelon: Political -- The Pure Basis of Politics -- Chapter 4 Nothing Writes: On Madame Guyon -- Against "Holy Indifference" -- Rectifying Fénelon -- "I am not allowed to continue here" -- Writing Scripture -- Nothing That Liberates -- Nothingness as Place -- Nothing Writes -- The Mystical (of the) Self -- Chapter 5 The Power to Say I: On Simone Weil -- Nothing but the I -- Religion for Slaves -- Redemptive Suffering -- "The irreducible basis of my suffering" -- Chapter 6 Contra‑Religious Religion: The Mystical Experience of a Modern Protestant Minister -- A Religious Experience? -- A Philosophical Experience? -- Being and Question -- Contra‑Religious … -- … Religion -- Philosophy / Religion -- Chapter 7 The Path of Mercy Means Simply that You Abandon Self: On a Novel by Shu¯saku Endo -- "Trample! Trample!" -- A Brief Genealogy of the Christian Ego as Self‑Denial -- Rodrigues's Doubt -- Chapter 8 As a Drop in the Ocean: Michel de Certeau's Selfless Christianity -- Christianity, a New Mythology? -- Christianity's rupture instauratrice -- A Subversive Drop of Water in the Sea -- Frame of Reference: One Way -- Frame of Reference: The Other Way Around.